2007
DOI: 10.1007/s00592-007-0014-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pioglitazone on heart function and N-terminal pro-brain natriuretic peptide levels of patients with type 2 diabetes

Abstract: We assessed the effect of the addition of pioglitazone on metabolic control and heart function of patients with type 2 diabetes already receiving sulfonylurea plus metformin. Forty-four patients were given 30 mg of pioglitazone for 3 months. Physical examination, laboratory tests including N-terminal pro-brain natriuretic peptide (NT-proBNP), and echocardiography, were performed at baseline and at study completion. Target HbA(1c) levels were achieved by 44.2% of the patients. Pioglitazone ameliorated lipid pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…The cardiotoxic effects of high doses of rosiglitazone were recently shown to be largely PPARγ-independent and involve mitochondrial dysfunction (He et al, 2014). In human studies, TZDs are associated with lipid accumulation in cardiomyocytes (Marfella et al, 2009), but pioglitazone showed no effect or even beneficial effects on echocardiographic measures of cardiac function (Horio et al, 2005; Sambanis et al, 2008). TZDs are not generally thought to cause cardiomyopathy directly, but rather to exacerbate heart failure via fluid retention in susceptible patients.…”
Section: Fluid Retention Edema and Congestive Heart Failure Due To Tzdsmentioning
confidence: 99%
“…The cardiotoxic effects of high doses of rosiglitazone were recently shown to be largely PPARγ-independent and involve mitochondrial dysfunction (He et al, 2014). In human studies, TZDs are associated with lipid accumulation in cardiomyocytes (Marfella et al, 2009), but pioglitazone showed no effect or even beneficial effects on echocardiographic measures of cardiac function (Horio et al, 2005; Sambanis et al, 2008). TZDs are not generally thought to cause cardiomyopathy directly, but rather to exacerbate heart failure via fluid retention in susceptible patients.…”
Section: Fluid Retention Edema and Congestive Heart Failure Due To Tzdsmentioning
confidence: 99%
“…On the other hand, clinical studies have demonstrated a neutral effect of pioglitazone on cardiac structure and systolic function in DM2 patients with normal [15] or impaired systolic function [16] using conventional echocardiography. The effects of pioglitazone on echocardiographic indices in patients with DM2 and LVDD have not been largely studied, while Tissue Doppler Imaging (TDI) echocardiography that allows more direct quantification of LV diastolic function [17] has been very little used in this context [18].…”
Section: Introductionmentioning
confidence: 99%
“…One probable explanation is the result of increased cardiac wall stretch caused by volume retention which is considered as the main adverse event of TZD therapy. Christos Sambanis et al reported that pioglitazone does not alter echocardiographic parameters even though it increases NT-proBNP after a 3 month treatment period in 44 patients with T2DM, and speculated that it may represent a reaction to volume overload [27]. It has been suggested that serial monitoring changes in BNP levels over time is beneficial to potentially enable the detection of volume overload secondary to TZD use and the onset of cardiac dysfunction before echocardiographic changes [28].…”
Section: Discussionmentioning
confidence: 99%